Meta‐barcoded evaluation of the ISO standard 11063 DNA extraction procedure to characterize soil bacterial and fungal community diversity and composition. Issue 1 (4th September 2014) - Terrat, Sebastien; Plassart, Pierre; Bourgeois, Emilie; Ferreira, Stéphanie; Dequiedt, Samuel; Adele‐Dit‐De‐Renseville, Nathalie; Lemanceau, Philippe; Bispo, Antonio; Chabbi, Abad; Maron, Pierre‐Alain; Ranjard, Lionel
Summary This study was designed to assess the influence of three soil DNA extraction procedures, namely the International Organization for Standardization (ISO‐11063, GnS‐GII and modified ISO procedure (ISOm), on the taxonomic diversity and composition of soil bacterial and fungal communities. The efficacy of each soil DNA extraction method was assessed on five soils, differing in their physico‐chemical characteristics and land use. A meta‐barcoded pyrosequencing approach targeting 16S and 18S rRNA genes was applied to characterize soil microbial communities. We first observed that the GnS‐GII introduced some heterogeneity in bacterial composition between replicates. Then, although no major difference was observed between extraction procedures for soil bacterial diversity, we saw that the number of fungal genera could be underestimated by the ISO‐11063. In particular, this procedure underestimated the detection in several soils of the genera Cryptococcus, Pseudallescheria, Hypocrea and Plectosphaerella, which are of ecological interest. Based on these results, we recommend using the ISOm method for studies focusing on both the bacterial and fungal communities. Indeed, the ISOm procedure provides a better evaluation of bacterial and fungal communities and is limited to the modification of the mechanical lysis step of the existing ISO‐11063 standard.